Financial Literacy and Basic Accounting Understanding: The Foundation of Business Sustainability Through Business Culture - Nuril Badria; Naimatul Hasanah (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of financial literacy and basic accounting understanding on business sustainability, with culture as a mediating variable in Madura grocery stores in Malang City. The research method used a quantitative approach with a survey technique. The sampling technique used was purposive sampling, with 136 respondents. Data analysis was conducted using Partial Least Squares (PLS) using SmartPLS version 4 software. The results showed that financial literacy and basic accounting understanding had a positive and significant effect on business sustainability and business culture. Business culture was also shown to have a positive and significant effect on business sustainability. Furthermore, culture was shown to mediate the influence of financial literacy and basic accounting understanding on business sustainability. These findings confirm that financial literacy and good accounting understanding will shape a healthy business culture and ultimately strengthen business sustainability. This study provides implications for MSMEs (Micro, Small, and Medium Enterprises) to improve their financial literacy and accounting understanding, as well as build a positive business culture to maintain competitiveness and business sustainability.